Besaran dan Orientasi Bukaan Pencahayaan Alami Rumah untuk Kenyamanan Beraktivitas Selama Pandemi - Muntakilah, Silmi Novia; Rusyda, Hana Faza Surya (Program Studi Desain Interior Unikom, 2022)
ABSTRACT Natural lighting is an important indicator of building design. Many activities are currently laid off, so it’s critical the indoor can still be used comfortably as a place for activities. Sunlight entering the space optimally creates a good natural lighting system, but therefore an unwanted increase in temperature may occur. This study aims to determine the effectiveness of natural light on residential study objects. The quantitative method was carried out by collecting data from literature and observations on residential in the Buah Batu area, Bandung, each of which calculated the effectiveness of natural lighting in the inner space. The results of this study obtained the effectiveness of natural lighting in the living room of 517.6 lux with a north-facing orientation, a 445.6 lux master bedroom facing north, and a 280 lux children's bedroom with a west-facing orientation whose natural lighting level is by SNI standards in the living room and bedroom with a minimum of 150 to 250 lux. With the results of the study object in this study, it is hoped that the effective light hole factor and orientation in the design of the residential house are more considered so that the comfort of occupants' activities can be achieved. Keywords: residential house, natural lighting, space comfort, pandemic activities